Hydrothermal Synthesis and Crystal Structure of Thiophene-2,5-dicarboxylate Cobalt(II) - Zhao, Y.; Zhang, Y.D. (Asian Journal of Chemistry, 2015)
One new cobalt compound using Co(NO3)2·6H2O and thiophene-2,5-dicarboxylic acid with m.f. C12H16O15S2Co has been successfully synthesized. The compound has been characterized by X-ray single-crystal diffraction. The compound shows a one-dimensional framework. The 3D supramolecular structure is formed via hydrogen bonding connection.